Light-responsive azo-containing organogels. Issue 22 (26th May 2017) - Ayer, M. A.; Schrettl, S.; Balog, S.; Simon, Y. C.; Weder, C.
Abstract : An azo-based cross-linker reacts with poly(vinyl alcohol) to afford stimuli-responsive organogels that display an irradiation-induced solid-to-liquid phase transition. Abstract : While azo compounds are widely employed as radical initiators, they have rarely been used as stimuli-responsive motifs in macromolecular constructs. In this study, an azo-based cross-linker was prepared and reacted with poly(vinyl alcohol) to afford a series of stimuli-responsive organogels. Irradiation of these materials with UV light causes de-cross-linking and triggers a solid-to-liquid phase transition. Model adhesives with de-bonding-on-demand capability based on this design were explored.